Influence of the reagent types on the characteristics of barium hexaferrites prepared by mechanochemical method - Zhuravlev, Victor A.; Nevmyvaka, Anna A.; Itin, Volya I.; Svetlichnyi, Valerii A.; Lapin, Ivan N.; Wagner, Dmitriy V. (Materials today communications)
The phase composition, structure parameters, morphology and the basic magnetic characteristics of BaFe12O19 hexaferrites obtained by the method of soft mechanochemical synthesis with the following annealing in air for one hour at temperatures in the range from 800 to 1100 °C were studied. The influence of the reagent type on the phase composition and structural characteristics of hexaferrites are analyzed. It has been established that for the synthesis of a single-phase barium hexaferrite a reaction when only water-containing reagents are used is advantageous. In addition, the participation of water in the mechanochemical synthesis leads to an increase in the rate of reagent interaction. The saturation magnetization and the anisotropy fields were determined. The specific saturation magnetization of the sample obtained using the initial hydrous reagents (FeCl3·6H2O and BaCl2·2H2O) is higher than that of the sample obtained using the anhydrous barium chloride (BaCl2). Magnetocrystalline anisotropy of the synthesized materials is investigated by the ferromagnetic resonance method. Along with the high-anisotropic ВаM phase the samples contain the traces of a phase with a small field of magnetocrystalline anisotropy. It is caused by the presence of the X-ray amorphous phase in the samples. Another source of this phase is the superparamagnetic Ba-M hexaferrite nanoparticles. © 2019 Elsevier Ltd